THE CORRELATION AMONG WRITING INTEREST, LANGUAGE LEARNING STRATEGIES, AND PARAGRAPH WRITING ACHIEVEMENT - Manurung, Ria Maya Lestari; Mulyani, Destia Dwi; Magdalena (Universitas PGRI Palembang, 2025)
This research aims to determine the existence of a substantial association between language learning methodologies, writing interest, and paragraph writing achievement. The employed methodology was descriptive, and the design was correlational in nature. Forty-one students from STKIP Muhammadiyah Pagaralam were selected as the samples for this research. Two types of surveys and a paragraph writing achievement exam were conducted to gather the data. The research findings indicated that (a) a significant correlation existed between language learning strategies and paragraph writing achievement, (b) a significant correlation was found between writing interest and paragraph writing achievement, (c) a significant correlation was observed among language learning strategies, writing interest, and paragraph writing achievement, and (d) no significant correlation was identified between language learning strategies and writing interest. The finding indicates that language learning strategies and writing interest significantly correlate with the enhancement of paragraph writing achievement among sixth-semester students in the English education study program at STKIP Muhammadiyah Pagaralam.